Remote education during the COVID-19 emergency. Analysis of the experience of university students (2022)
Objective: To analyze the experience of students from Bogotá's public universities to the emergency remote education model, implemented as a result of the suspension of classes due to the Covid-19 pandemic. Originality/contribution: Its approach, focused on the experiences of the students, provides a wealth of information on the central actors of the educational process, evidencing some gaps between the discourse and the reality of remote education. Method: mixed, as it integrates qualitative and quantitative information. The closed questions were statistically processed, and their results were contrasted with the information obtained in the open questions and with the literature on the subject. Strategies/information collection: A virtual survey on the conditions of connectivity and the experience of the students under this model was used as a basic instrument for the collection of information. Conclusions: The main findings are: in the first place, it is confirmed that the need to access a computer permanently, with a quality internet connection, constitutes an obstacle that is difficult to solve for students, which generates frustration and demotivation. Second, it is evidenced that, for students, the Internet connection and the home environment are perceived as a source of distraction that prevents them from concentrating on their studies. Third, as a consequence of the previous two, the majority of students consider that the quality of education has decreased and believe that this will negatively impact their professional future.